NEW RECORDS OF THE BAT HAWKMOTH, HYLES VESPERTILIO (ESPER, 1780) (LEPIDOPTERA: SPHINGIDAE) IN CROATIA, BOSNIA AND HERZEGOVINA AND SERBIA (Acta Entomologica Serbica, 2022)
New records of Hyles vespertilio (Esper, 1780) are reported from Croatia, Bosnia and Herzegovina and Serbia. In Croatia, a single specimen was recorded on Mt. Biokovo, within the Biokovo Nature Park, southern Croatia. This is the first record in the country in 44 years. In Bosnia and Herzegovina, the species was recorded at 11 localities within or in the near surroundings of the Blidinje Nature Park. This species is new to the fauna of Bosnia and Herzegovina and is the 20th Sphingidae species recorded in the country. In Serbia, the species was recorded in Krajinoviće, Mt. Giljeva. This is the third known record and the first observation for this country in 32 years. The preferred host plant, Epilobium dodonaei, is present at all the studied localities in Croatia and Bosnia and Herzegovina, but the caterpillars were not surveyed during this work. These findings could be treated as resident populations of the bat hawkmoth, since the species is considered nonmigratory, and the host plant is present in the study areas.